The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1002/adma.201303467
|View full text |Cite
|
Sign up to set email alerts
|

Band‐Bending in Organic Semiconductors: the Role of Alkali‐Halide Interlayers

Abstract: Band-bending in organic semiconductors, occurring at metal/alkali-halide cathodes in organic-electronic devices, is experimentally revealed and electrostatically modeled. Metal-to-organic charge transfer through the insulator, rather than doping of the organic by alkali-metal ions, is identified as the origin of the observed band-bending, which is in contrast to the localized interface dipole occurring without the insulating buffer layer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
100
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 87 publications
(101 citation statements)
references
References 55 publications
1
100
0
Order By: Relevance
“…[4]- [6] In addition, the ensuing negative charges in the organic layer lead to an upward band bending. [4] The benefits of Fermi level pinning at electrode interfaces for device performance that have been demonstrated include an increase in carrier injection efficiency, [7] as well as less sshaped behavior in current density-voltage characteristics of organic photovoltaic cells. [8] One of the simplest ways to lower the electrode WF is the thermal deposition of an ultrathin metal layer of groups 1 or 2, such as calcium, onto an electrode.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[4]- [6] In addition, the ensuing negative charges in the organic layer lead to an upward band bending. [4] The benefits of Fermi level pinning at electrode interfaces for device performance that have been demonstrated include an increase in carrier injection efficiency, [7] as well as less sshaped behavior in current density-voltage characteristics of organic photovoltaic cells. [8] One of the simplest ways to lower the electrode WF is the thermal deposition of an ultrathin metal layer of groups 1 or 2, such as calcium, onto an electrode.…”
Section: Introductionmentioning
confidence: 99%
“…It should also be noted that the obtained WF is sufficiently lower than electron affinities of most electron transport materials (3-5 eV). [35]- [36] Consequently, this energetic scenario will lead to LUMO level pinning with typical electron transport materials [4]- [6] and a minimum electron injection barrier can be assured for their contacts. One might speculate that 1 + and/or 1 2 diffuse into an organic film deposited on the modified substrate, as demonstrated for a pdopant.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4,[6][7][8][9] However, the bandgap and electronics structures at the interfacial region, where two materials are in contact with each other, can differ from the bulk, because of interfacial interactions. [10][11][12][13][14] Therefore, robust and direct methods are needed to probe the band gaps as well as electronic structures at buried interfaces.…”
Section: Introductionmentioning
confidence: 99%
“…For example, UV photoelectron spectroscopy 7,11,14 or Ballistic-Electron-Emission Microscopy 15 can determine the band alignment at interfaces of films with precisely-controlled thickness. It is found that in the films that are a few molecules thick, electron tunneling between two domains significantly changes the electronic structures of the molecules at interfaces 16,17 .…”
Section: Introductionmentioning
confidence: 99%